Green‐shifting of SWS2A opsin sensitivity and loss of function of RH2‐A opsin in flounders, genus Verasper. Issue 2 (27th December 2017) - Kasagi, Satoshi; Mizusawa, Kanta; Takahashi, Akiyoshi
Abstract: We identified visual opsin genes for three flounder species, including the spotted halibut ( Verasper variegatus ), slime flounder ( Microstomus achne ), and Japanese flounder ( Paralichthys olivaceus ). Structure and function of opsins for the three species were characterized together with those of the barfin flounder ( V. moseri ) that we previously reported. All four flounder species possessed five basic opsin genes, including lws, sws1, sws2, rh1, and rh2 . Specific features were observed in rh2 and sws2 . The rh2‐a, one of the three subtypes of rh2, was absent in the genome of V. variegatus and pseudogenized in V. moseri . Moreover, rh2‐a mRNA was not detected in M. achne and P. olivaceus, despite the presence of a functional reading frame. Analyses of the maximum absorption spectra (λmax ) estimated by in vitro reconstitution indicated that SWS2A of M. achne (451.9 nm) and P. olivaceus (465.6 nm) were blue‐sensitive, whereas in V. variegatus (485.4 nm), it was green‐sensitive and comparable to V. moseri (482.3 nm). Our results indicate that although the four flounder species possess a similar opsin gene repertoire, the SWS2A opsin of the genus Verasper is functionally green‐sensitive, while its overall structure remains conserved as a blue‐sensitive opsin. Further, the rh2‐a function seems to have been reduced during the evolution of flounders. λmax values of predicted ancestral SWS2A of Pleuronectiformes and Pleuronectidae was 465.4 and 462.4 nm, respectively, indicating that these were blue‐sensitive. Thus, the green‐sensitive SWS2A is estimated to be arisen in ancestral Verasper genus. It is suggested that the sensitivity shift of SWS2A from blue to green may have compensated functional reduction in RH2‐A. Abstract : In this study, we demonstrate that SWS2A opsin—originally blue‐sensitive opsin—is green‐sensitive in genus Verasper flounder, while one of the green‐sensitive opsin RH2‐A is losing its function in this lineage. It is suggested that the sensitivity shift of SWS2A from blue to green might compensate functional reduction of RH2‐A.